Plastic waste collection route optimization: Bulgan province - Dembereldash, Enkhbaatar; Batbaatar, Uyanga; Tuuguu, Enkhdul; Batzorig, Sanchirgarav (Mongolian Journal of Geography and Geoecology, 2025)
Efficient plastic waste collection in rural Mongolia is critical to reducing environmental pollution and improving recycling outcomes. This study optimizes plastic waste transport routes in Bulgan province using the travelling salesman problem (TSP), and vehicle routing problem (VRP) algorithms and open-source GIS tools. By analyzing population data, waste generation rates, and vehicle capacity, ten optimal routes were identified for 15-ton load serving 19 key locations. Results show large disparities in route efficiency, with urban centers generating more waste per kilometer than sparsely populated areas. Recommendations include dynamic routing, vehicle load capacity, and investing in local waste compacting equipment. The findings offer practical solutions for cost-effective, sustainable rural waste management.